Recent trends in internal migration in Nuevo Leon, Mexico - Bedoya Rangel, Yuliet; Jáuregui Díaz, José Alfredo; Avila Sánchez, María de Jesús; Picazzo Palencia, Esteban (Universidad Autónoma de Chiapas, 2018)
Nuevo León State, Mexico, has historically been a pole of population attraction at the national level, the population growth recorded in this geographic space during the last 50 years is largely a product of immigration processes, stimulated by economic growth of a growing industrial sector, which generated a labor demand that without the arrival of population from other parts of the country would not have been possible to cover. This research presents the recent trends of immigration in Nuevo León using as a primary source of information the Intercensal Survey 2015 of the National Institute of Statistics and Geography (inegi), which analyzes some contextual variables such as sex, age, Indigenous speaking status and schooling. As a reference, data derived from the 1970, 1990, 2000 and 2010 censuses are also used, because it is not possible to understand the present without understanding the past.